Animal Choice Behavior. - Mazur, James (Fall ; Psychology., 1995)
Keywords: dept.psy; faculty_collection; sabbatical_report

Psychology and the Law. - Tolchin, Gerald (1991)
Keywords: dept.psy; faculty_collection; sabbatical_report

Guide for Psychology Majors: A Student Handbook. - Flannelly, Linda (1990)
Keywords: dept.psy; faculty_collection; sabbatical_report

Revision of an Interactive Computer Program. - Harmon, Duane (1990)
Keywords: dept.psy; faculty_collection; sabbatical_report

(MMPI and Rorschach) - Muller, Bruce (1990)
Keywords: dept.psy; faculty_collection; sabbatical_report

Extending the Developmental Interpretation of Delusions and Hallucinations.. - Glick, Marion (1988)
Keywords: dept.psy; faculty_collection; sabbatical_report

When to Forgive - Affinito, Mona Gustafson (New Harbinger Publications, 1999)
Keywords: Forgiveness; dept.psy; faculty_collection

Helping with Forgiveness Decisions: A Brief Guide for Counselors - Affinito, Mona Gustafson (Manisses Communications Group, Inc., 1998)
Keywords: Forgiveness; dept.psy; faculty_collection

The Nature of Visual Illusion - Fineman, Mark B. (Dover Publications, 1996)
Keywords: Problems, exercises, etc; Visual perception; Visual perception; dept.psy; faculty_collection

Learning and Behavior - Mazur, James E. (Prentice Hall, 1994)
Keywords: Learning, Psychology of; Conditioned response; Behavior modification; Psychology, Comparative; dept.psy; faculty_collection

Behavior Modification - Sherman, William M. (Harper & Row, 1990)
Keywords: Behavior modification; dept.psy; faculty_collection

The Copts Since the Arab Invasion: Strangers in Their Land - Karas, Shawky F. (American, Canadian, and Australian C. Coptic Associations, 1985)
Keywords: 1952-1970; Copts; Egypt; Ethnic relations; Egypt; Politics and government; dept.psy

The Inquisitive Eye - Fineman, Mark B. (Oxford University Press, 1981)
Keywords: Problems, exercises, etc; Visual perception; Visual perception; dept.psy; faculty_collection

Parent Conferences in the Schools: Procedures for Developing Effective Partnership - Losen, Stuart M.; Diament, Bert; Losen, Joyce Garskof (Allyn and Bacon, 1978)
Keywords: Parent-teacher conferences; dept.psy; faculty_collection

"Facilitation of Stereoscopic Depth Perception by a Relative-Size Cue in Ambiguous Disparity Stereograms": Erratum - Fineman, M.B. (Journal of Experimental Psychology, 1972)
Reports an error in the original article by Mark B. Fineman (Journal of Experimental Psychology, 1971[Oct], 90[2]], 215-221). Fig. 1 and Fig. 2 on pp. 216 and 217 were shown inverted. This mistake made it appear that Stimulus 1 was Stimulus 2, and that Stimulus 3 was Stimulus 4, and that the four stimuli were upside down. (The following abstract of this article originally appeared in record.) Proposed that the cue of relative size may facilitate depth perception in accordance with a crossed or uncrossed disparity in stereograms in which both tendencies are equally represented. A concurrent concept was that the latency associated with the perception of depth in random-dot stereograms may be due, in part, to a cue conflict between binocular disparity and relative size. 4 male and 2 female graduate students were given 8 presentations of 5 stereographic stimuli, in which disparity was ambiguous but relative size was systematically altered. Ss were tested for direction of depth preferences and response latency. Both the relative-size effects and an uncrossed disparity bias were evidenced in the data. The latter effect was attributed to binocular rivalry between dissimilar elements in the stereoscopic half-fields. It is concluded that depth cue relationships are more complex than had been suggested by simple dominance theories. (PsycINFO Database Record (c) 2006 APA, all rights reserved). © 1972 American Psychological Association.
Keywords: ambiguous disparity stereograms; dept.psy; relative size cue; stereoscopic depth perception facilitation

The Need to Test Hypotheses About Paranoid Schizophrenia: Reply to Clementz and Sweeney - Glick, M.; Zigler, E. (American Psychologist, 1989)
Keywords: Depressive Disorder; Diagnosis, Differential; Human; Psychiatric Status Rating Scales; Schizophrenia, Paranoid; article; depression; dept.psy; differential diagnosis; human; paranoid schizophrenia; psychological aspect; rating scale

Choice Behavior in Transition: Development of Preference With Ratio and Interval Schedules - Mazur, J.E. (Journal of Experimental Psychology: Animal Behavior Processes, 1992)
In Experiment 1, the choice responses of 8 pigeons were observed during 50 periods of transition. Each condition began with equal probabilities of reinforcement on 2 response keys and switched to unequal probabilities. With the ratio of the 2 probabilities held constant, preference for the higher probability developed more rapidly when the 2 probabilities were high than when they were low. In Experiment 2, each condition began with 2 equal variable-interval schedules, but later 1 key delivered 60%, 75%, or 90% of the reinforcers. The rate of approach to asymptotic performance was roughly the same with all 3 reinforcement percentages. These and previous results pose difficulties for some well-known models of acquisition, but the results are well described by a simple model that states that the strength of each response is independently increased by reinforcement and decreased by nonreinforcement.
Keywords: Animal; Attention; Choice Behavior; Color Perception; Motivation; Orientation; Pigeons; Probability Learning; Problem Solving; Reinforcement Schedule; Support, U.S. Gov't, P.H.S.; animal; article; attention; color vision; decision making; dept.psy; learning; motivation; orientation; pigeon; problem solving; reinforcement

A profile analysis of psychopathology in clusters of depersonalization types - Jacobs, J.R.; Bovasso, G. (Dissociation, 1996)
Five types of depersonalization experiences based on scales developed by Jacobs and Bovasso (1992) were used to cluster subjects into six groups. Four relatively small groups which had regular depersonalization experiences were identified: the Derealized, the Self-negating, the Body-detached, and the Profoundly Depersonalized. The fifth group, the Fleetingly Depersonalized, and the sixth group, the Non-depersonalized, constituted 25% and 50% of the population, respectively. A profile analysis indicated qualitative differences between the six groups in their pathological traits, which fell along a continuum of pathological severity. The results support the validity of a multidimensional depersonalization construct which may clarify some of the contradictions and inconsistencies in the literature on depersonalization. Further, the results may facilitate clinicians' differentiation of their patients along a continuum of pathological severity based on the type and frequency of depersonalization experiences which they report.
Keywords: dept.psy; ⛔ No DOI found

The three-dimensional graphic method for quantifying body position - Trochim, William M K (Behavior Research Methods, 1976)
The three-dimensional graphic method for quantifying body position is a series of observer procedures and computer programs designed to yield three-dimensional (height, width, and depth) coordinates for various body points. These coordinates can be graphed by computer in several different ways, and can be analyzed mathematically to provide information about a wide variety of variables, including interpersonal distance and body activity. The procedure for collecting and analyzing the data is explained and the computer programs developed for the method are described. © 1976 Psychonomic Society, Inc.
Keywords: dept.psy

Sensory World - Introduction to Sensation and Perception - Bennett,tl - Fineman, MB (Contemporary Psychology, 1979)
Keywords: dept.psy; ⛔ No DOI found

Environmental Noise in a Residential Institution for Mentally-Retarded Persons - Glenn, LE; Nerbonne, GP; Tolhurst, GC (American Journal of Mental Deficiency, 1978)
Keywords: dept.psy; ⛔ No DOI found

The effect of a moving dot transversal on the Poggendorff illusion - Fineman, Mark B; Melingonis, Mark P (Attention Perception & Psychophysics, 1977)
In attempting to derive the minimal component of the Poggendorff figure which would still produce an illusion, responses to three types of transversal were measured. One was the customary solid line type; a second type presented the two segments sequentially, alternating between them; and the third consisted of a moving dot which traveled the transversal path. Each transversal was shown with and without verticals, for a total of six conditions. Ten subjects in each condition adjusted the luminous transversal until the segments appeared to be collinear. Figures with verticals present showed a greater magnitude of illusion than those without, and discrepancies for moving dot transversals were greater than those for comparable solid line figures. Since alternating transversals were not significantly larger than solid line figures, it was concluded that the magnitude of the moving dot effect could not be attributed to temporal sequence. An eyemovement hypothesis was suggested instead. © 1977 Psychonomic Society, Inc.
Keywords: dept.psy; normal human; theoretical study; visual illusion

Egypts Christian Minority - Karas, SF (Middle East Review, 1977)
Keywords: dept.psy; ⛔ No DOI found

Primitive Drive-Dominated Thinking - Relationship to Acute Schizophrenia and Sociopathy - Harrow, M; Quinlan, D; Wallington, S; Pickett, L (Journal of Personality Assessment, 1976)
Keywords: dept.psy

A comparison of the Ponzo illusion with a textural analogue - Fineman, Mark B; Carlson, Jeffrey (Attention Perception & Psychophysics, 1973)
The inappropriate constancy scaling notion of geometric illusions was explored by employing a textural analogue of the Ponzo figure. Ten Ss estimated the length of a horizontal line by equating it with varying companion lines in the context of the Ponzo figure, a textural analogue, and a baseline control in which the lines appeared with no surrounding contours. The textural analogue had the added feature of imposing no contours at the ends of the horizontal lines. It was found that length estimates were significantly different between the horizontals of the Ponzo figure and control stimuli, but not between the texture figure and a context-free control. The results suggest that inappropriate constancy scaling plays a minor role at best in the perception of geometric illusions. © 1973 Psychonomic Society, Inc.
Keywords: dept.psy; normal human; theoretical study; visual illusion

Consequences of transgression: self-punishment and depression. - Wallington, Sue A (Journal of Personality and Social Psychology, 1973)
Assessed the effects of transgression on self-aggression and depression in 96 high school students. Male confederates induced 1/2 of the Ss to transgress by deceiving the E. As a measure of self-aggression all Ss gave themselves electric shocks of intensity which they personally selected. Ss were also given behavioral and subjective-report measures of depression, including the Mood Adjective Check List. Transgressing Ss showed significantly more self-aggression. Transgressing Ss also showed changes on behavioral measures of depression but not on subjective-report measures. Females showed significantly more self-aggression than males regardless of condition. Findings suggest that the altruistic behavior found to occur after transgression may be engaged in for its self-punitive aspect as well as, or rather than as, a means of social restitution, as has been previously suggested. Contrary to the suggestion of some theories of depression, self-punishment did not appear to alleviate depression. (21 ref) (PsycINFO Database Record (c) 2006 APA, all rights reserved). © 1973 American Psychological Association.
Keywords: Aggression; Depression; Electroshock; Female; Guilt; Human; Male; Morals; Orientation; Personality Inventory; Psychological Theory; Punishment; Self Concept; Sex Factors; Social Behavior; aggression; article; depression; depression, high school students; dept.psy; electric shock; female; guilt; human; male; morality; orientation; personality test; psychological theory; punishment; self concept; sex difference; social behavior; transgression, self-aggression &

Drug abuse and television viewing patterns - Brodlie, Jerome F. (Psychology, 1972)
Keywords: dept.psy; ⛔ No DOI found

The effectiveness of a sex education program on the teacher's sex knowledge and attitudes - Karas, Shawky F; Elliot, Gale Ann (Small Group Research, 1972)
Keywords: dept.psy

The influence of communicator-recipient similarity upon the beliefs and behavior of pregnant women - Mazen, Ragaa; Leventhal, Howard (Journal of Experimental Social Psychology, 1972)
A field experiment was conducted to investigate the effects of communicator-recipient similarity and verbal communication upon the attitudes and behavior of pregnant women. Similarity was varied on two dimensions, pregnancy and color; and these factors were crossed with three communication conditions: (1) information on the advantages of rooming-in and breast feeding; (2) information combined with personal endorsement; and (3) no-information control. Both a pilot study and the main experiment showed no important differences in the amount of attitude change or behavioral compliance between the communication conditions. There were also no significant differences in attitude change as a function of similarity in pregnancy. However, a significantly higher proportion of mothers breast fed and roomed-in when the communicator was pregnant and similar than when she was nonpregnant and dissimilar. Similarity in color had no effect upon attitudes or behavior for the topic of rooming-in. But when the communicator was dissimilar in color there was significant negative change in attitudes toward breast feeding. Similarity in color also increased breast feeding. Attitudes and actions were related; mothers with initially favorable attitudes were more likely to comply for both issues. But with only one exception, attitude change was unrelated to behavioral compliance. The results are discussed in terms of visible similarity as a source of information or cues for action. © 1972.
Keywords: dept.psy

Facilitation of stereoscopic depth perception by a relative-size cue in ambiguous disparity stereograms. - Fineman, Mark B. (Journal of Experimental Psychology, 1971)
Proposed that the cue of relative size may facilitate depth perception in accordance with a crossed or uncrossed disparity in stereograms in which both tendencies are equally represented. A concurrent concept was that the latency associated with the perception of depth in random-dot stereograms may be due, in part, to a cue conflict between binocular disparity and relative size. 4 male and 2 female graduate students were given 8 presentations of 5 stereographic stimuli, in which disparity was ambiguous but relative size was systematically altered. Ss were tested for direction of depth preferences and response latency. Both the relative-size effects and an uncrossed disparity bias were evidenced in the data. The latter effect was attributed to binocular rivalry between dissimilar elements in the stereoscopic half-fields. It is concluded that depth cue relationships are more complex than had been suggested by simple dominance theories. (PsycINFO Database Record (c) 2006 APA, all rights reserved). © 1971 American Psychological Association.
Keywords: Conflict (Psychology); Cues; Depth Perception; Female; Form Perception; Human; Male; Reaction Time; Size Perception; Vision; article; association; conflict; dept.psy; depth perception; female; human; male; pattern recognition; perception; reaction time; steroscopic depth perception facilitation, relative-size cue in ambiguous disparity stereograms; vision

Student teachers as tutors for children in an inner city school - Levine, Murray; Dunn, Freda; Brochinsky, Steve; Bradley, Jesse; Donlan, Kay (Child Psychiatry & Human Development, 1970)
A tutoring program for first grade inner city children, employing student teachers as tutors, was developed and evaluated. Tutoring had no discernible effects on performance on the Illinois Test of Psycholinguistic Ability. However, tutored children were placed in the highest reading group, and were rated by the regular classroom teacher as having completed the first grade reading series more often than controls. Tutors saw their children as becoming more responsive over time. Classroom teachers rated the tutored children as more competent in the classroom, more confident, and as viewing the classroom as more benevolent. In contrast to controls, student teachers maintained favorable attitudes toward teaching in the inner city, and they claimed to have benefited in practice teaching from their tutoring experience. However, relatively few actually took teaching positions in inner city schools after completing their training. © 1972 Behavioral Publications, Inc.
Keywords: dept.psy

The mental patient and civil rights: Some moral, legal, and ethical considerations. - Tolchin, Gerald; Steinfeld, George; Suchotliff, Leonard (Professional Psychology, 1970)
Distinguishes between legal, ethical, and egalitarian principles involving hospitalization of persons alleged to be mentally ill. With regard to the question of legality, the need for compilation and distribution of relevant information and for informing patients of their rights is discussed. The boundaries of psychologists' professional and personal ethics are viewed as helping patients obtain services which they are personally unable to provide and insuring that the welfare of the patient is placed before the interests of the institution. Egalitarian issues are discussed with regard to: (a) judging whether a mental patient is responsible for his words and actions; (b) the patient's right to accept, reject, or select treatment; and (c) hospitalization of general medical patients and their rights to be informed about their condition, to be notified of test results, and to know the name, quantity, and expected reaction to drugs they are given. It is suggested that psychologists have too long been silent on these issues and in the face of abuses, and that more discussion and stands on them are needed. (PsycINFO Database Record (c) 2006 APA, all rights reserved). © 1970 American Psychological Association.
Keywords: dept.psy; moral vs. legal vs. ethical considerations regarding hospitalization of mentally ill

Development of a reduced set of composite equations for three predictors - Karas, Siiawky F (Psychological Reports, 1969)
Keywords: dept.psy

The analysis of means techniques - Karas, Shawky F (Journal of Experimental Education, 1968)
The theoretical basis for the Analysis of Means Technique is discussed. In addition, a simplified working procedure is outlined, step-by-step for an actual problem. The data for the problem are analyzed by the analysis of means techniques, which compares differences between means instead of population variances estimates. The data are also analyzed by the analysis of variance technique. The conclusions reached by both techniques are the same. The graphical representation of the ANOM is helpful in understanding data. The ANOM technique is usually used in conjunction with the analysis of variance, either as an initial analysis of data or to augment the analysis of variance. © Taylor & Francis Group, LLC.
Keywords: dept.psy

Preventing maladjustment from infancy through adolescence - rickel,au, allen,l - Glick, M (Contemporary Psychology, 1989)
Keywords: dept.psy

Theories of probabilistic reinforcement. - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1989)
In three experiments, pigeons chose between two alternatives that differed in the probability of reinforcement and the delay to reinforcement. A peck at a red key led to a delay of 5 s and then a possible reinforcer. A peck at a green key led to an adjusting delay and then a certain reinforcer. This delay was adjusted over trials so as to estimate an indifference point, or a duration at which the two alternatives were chosen about equally often. In Experiments 1 and 2, the intertrial interval was varied across conditions, and these variations had no systematic effects on choice. In Experiment 3, the stimuli that followed a choice of the red key differed across conditions. In some conditions, a red houselight was presented for 5 s after each choice of the red key. In other conditions, the red houselight was present on reinforced trials but not on nonreinforced trials. Subjects exhibited greater preference for the red key in the latter case. The results were used to evaluate four different theories of probabilistic reinforcement. The results were most consistent with the view that the value or effectiveness of a probabilistic reinforcer is determined by the total time per reinforcer spent in the presence of stimuli associated with the probabilistic alternative. According to this view, probabilistic reinforcers are analogous to reinforcers that are delivered after variable delays. 1989 Society for the Experimental Analysis of Behavior
Keywords: Animal; Color Perception; Conditioning, Operant; Mental Recall; Probability Learning; Reinforcement Schedule; Support, U.S. Gov't, P.H.S.; adjusting schedule; animal; article; color vision; conditioned reinforcement; dept.psy; instrumental conditioning; intertrial interval; key peck; learning; pigeons; recall; reinforcement; reinforcer delay; reinforcer probability

The need to test hypotheses about paranoid schizophrenia: reply to Clementz and Sweeney. - Glick, Marion; Zigler, Edward (American Psychologist, 1989)
Keywords: dept.psy

Depression: A failure to suppress the self-conscious ‘Monitoring’ of dismal cognitions - Kunzendorf, Robert G; Mclaughlin, Susan (Imagination, Cognition and Personality, 1989)
Keywords: dept.psy

Is paranoid schizophrenia really camouflaged depression - Zigler, Edward; Glick, Marion (American Psychologist, 1988)
Keywords: dept.psy

Effect of lysine-8-vasopressin on retention and retrieval of a discrimination reward task in the rat. - Mulvey, Debra J; Watt, Jean M; Mcewen, Barbara B; Flannelly, Linda M (Behavioral Neuroscience, 1988)
The effect of vasopressin on memory of a brightness discrimination reward task was investigated in 20 male Sprague-Dawley rats. Two measures of retention were used: resistance to extinction and savings scores on a reacquisition task given 45 days after the completion of extinction training. The effect of the peptide on both memory consolidation and retrieval was assessed. There were two major findings: (a) The peptide enhanced memory consolidation of the task whether measured after a short time interval (6 days) or after a long time interval (45 days after completion of extinction training) using a measure of trials to relearn the task, and (b) the peptide had no effect on memory retrieval. These results were compared to those of other studies designed to access memory consolidation and retrieval on appetitive tasks. The mechanisms of the peptide's effect on memory was briefly discussed with respect to three theories on the subject. This study extends the vasopressin research on memory consolidation by suggesting that it pertains to appetitive as well as to aversive tasks.
Keywords: Animal; Appetitive Behavior; Brain; Conditioning, Operant; Discrimination Learning; Extinction (Psychology); Lypressin; Male; Memory; Mental Recall; Motivation; Orientation; Rats; Rats, Inbred Strains; Retention (Psychology); animal experiment; controlled study; dept.psy; lypressin; male; memory consolidation; memory retrieval; nonhuman; psychological aspect; psychophysiology; rat; reward

Premorbid competence, role orientation, and gender differences in DSM-II versus DSM-III schizophrenic patients. - Glick, Marion; Quinlan, Donald M; Zigler, Edward (Journal of Consulting and Clinical Psychology, 1987)
The study compared 71 patients diagnosed as schizophrenic or within the schizophrenia spectrum according to the second edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-II) with 66 patients who received similar diagnoses according to the third edition of the same manual (DSM-III). On measures of premorbid competence and role orientation, DSM-II and DSM-III schizophrenic patients obtained comparable scores. The DSM-III patients with schizophrenic versus schizophrenia spectrum diagnoses also obtained comparable scores on these measures. The gender differences in premorbid competence and role orientation that have consistently characterized DSM-II schizophrenics continued to characterize DSM-III schizophrenic and schizophrenia spectrum patients. The results suggest that findings previously obtained with DSM-II schizophrenics concerning premorbid competence and role orientation can be generalized to DSM-III schizophrenics. © 1987 American Psychological Association.
Keywords: adult; classification; competence; dept.psy; gender; human; major clinical study; orientation; schizophrenia

Effectiveness of the Mini-Mult in detecting MMPI pathology in the blind - Needham, Walter E.; Ehmer, Marjy N.; Marchesseault, Linda; l'Aune, William R. De (Journal of Clinical Psychology, 1986)
The Mini‐Mult and MMPI were administered in random order to 60 blind male veterans admitted to a residential rehabilitation program. Mini‐Mult scores predicted the presence or absence of MMPI pathology in 81.7% of the cases. Correlations between the individual Mini‐Mult and MMPI scales were significant at the p < .01 level, but not of sufficient magnitude to permit their interchangeability or to allow for profile diagnosis on the basis of Mini‐Mult scores. Analysis of the false negatives raises questions about the clinical significance of an abnormal MMPI in the population studied. The results support the value of the Mini‐Mult as a screening device, but not as a substitute for a detailed psychological assessment of the blind. Copyright © 1986 Wiley Periodicals, Inc., A Wiley Company
Keywords: Blindness; Human; MMPI; Male; Mass Screening; Mental Disorders; Middle Age; adult; blindness; central nervous system; clinical article; dept.psy; human; priority journal; psychological aspect; rehabilitation; visual system

Premorbid social competence and psychiatric outcome in male and female nonschizophrenic patients - Glick, Marion; Zigler, Edward (Journal of Consulting and Clinical Psychology, 1986)
The relation between premorbid social competence and outcome was examined in 448 (228 male and 220 female) first-admission, nonschizophrenic, state-hospital patients. For both sexes, higher social competence was related to more favorable outcome as reflected in shorter initial hospitalizations and shorter rehospitalizations. Consistent with a developmental formulation, these results provide further evidence that the relation between premorbid competence and outcome is not unique to schizophrenia but can be found for patients of both sexes across a range of diagnoses. © 1986 American Psychological Association.
Keywords: adult; central nervous system; clinical article; competence; dept.psy; human; mental patient; psychological aspect; social aspect; social behavior; therapy

Young-children reinvent arithmetic - implications of piaget theory - kamii,ck, declark,g - Smith, JP (Teachers College Record, 1986)
Keywords: dept.psy; ⛔ No DOI found

Developmental correlates of age at first hospitalization in nonschizophrenic psychiatric patients - Glick, M.; Zigler, E.; Zigler, B. (Journal of Nervous and Mental Disease, 1985)
Age at first hospitalization, premorbid social competence, and developmental categorizations of symptomatology were examined in 228 male and 220 female patients in three diagnostic categories: Major affective disorder, neuroses, and personality disorder. High social competence patients were older at first hospitalization than low competence individuals. Younger first admission patients showed more symptoms in the action category and in the role orientation of turning against others. Older patients more frequently displayed symptoms of the thought variety and of turning against the self. Gender differences in age at first hospitalization were not found. With respect to all developmental variables examined, the results suggest that a broader view of prognosis proposed in research with schizophrenic patients is applicable to nonschizophrenic groups. © 1985 by The Williams & Wilkins Co.
Keywords: Adult; Age Factors; Female; Hospitalization; Human; Male; Marriage; Mental Disorders; Middle Age; Mood Disorders; Neurotic Disorders; Occupations; Personality Disorders; Prognosis; Role; Sex Factors; Social Adjustment; Support, Non-U.S. Gov't; Support, U.S. Gov't, P.H.S.; affective neurosis; age; central nervous system; clinical article; dept.psy; hospitalization; human; mental patient; neurosis; personality disorder; priority journal; psychological aspect; social aspect; sociology

Paranoid schizophrenia: An unorthodox view. - Zigler, Edward; Glick, Marion (American Journal of Orthopsychiatry, 1984)
Keywords: dept.psy

Parent diary - a technique for sampling the expressive language of hearing-impaired children - Kessler, ME (Volta Review, 1983)
Keywords: dept.psy; ⛔ No DOI found

Complexity of context and orientation of figure in the corridor illusion - Fineman, Mark B (Perceptual and Motor Skills, 1981)
Keywords: dept.psy

Comparison of competitive trait anxiety levels of 9-12-year-old participants in little league and neighborhood baseball - Finn, JA; Sprague, LK (International Journal of Sport Psychology, 1981)
Keywords: dept.psy; ⛔ No DOI found

Premorbid social competence and the revolving door phenomenon in psychiatric hospitalization - Marsh, A.; Glick, M.; Zigler, E. (Journal of Nervous and Mental Disease, 1981)
The relation between premorbid social competence and length of initial hospitalization was examined in 381 male state hospital patients in four diagnostic categories: Schizophrenic, affective reaction, psychoneurotic, and personality disorder. A significant relation was discovered between diagnosis and outcome, with schizophrenic patients having the longest and personality disorder patients the shortest lengths of initial hospitalization. Premorbid social competence was related to outcome, as assessed both by length of initial hospitalization, and by whether the patient was rehospitalized. These two outcome measures were found to be positively related, thus supporting the developmental formulation that premorbid social competence is indicative generally of prognosis. The findings were employed to generate the inference that patients at differing levels of premorbid social competence require different treatment modalities. © 1981 by The Williams & Wilkins Co.
Keywords: Adult; Hospitals, Psychiatric; Human; Length of Stay; Male; Mental Disorders; Mood Disorders; Neurotic Disorders; Personality Disorders; Recurrence; Schizophrenia; Social Adjustment; central nervous system; dept.psy; major clinical study; mental hospital; personality disorder; schizophrenia; sociology

Inter-relationships among hospitalization measures of psychiatric outcome - Glick, M.; Marsh, A.; Zigler, E. (Journal of Nervous and Mental Disease, 1980)
In a diagnostically heterogeneous sample of 381 first admission male state hospital patients, no consistent correlations appeared among three commonly employed hospitalization measures of outcome. The possibility that psychiatric hospitalization may be a multidimensional criterion is considered and the implications for outcome research are discussed. © 1980 by The Williams & Wilkins Co.
Keywords: Follow-Up Studies; Hospitalization; Human; Length of Stay; Male; Mental Disorders; Models, Theoretical; Patient Readmission; Support, U.S. Gov't, P.H.S.; central nervous system; dept.psy; hospitalization; major clinical study; therapy

Irrational thinking and adjustment to loss of vision - Needham, WE; Ehmer, MN (Journal of visual impairment & blindness, 1980)
Keywords: dept.psy

Premorbid Social Competence and Outcome among Schizophrenic and Nonschizophrenic Patients - Zigler, Edward; Glick, Marion; Marsh, Anna (The Journal of Nervous and Mental Disease, 1979)
The relation between premorbid social competence and outcome was examined with 381 male state hospital patients in four diagnostic categories: schizophrenia, affective reaction, psychoneurotic disorder, and personality disorder. Outcome was assessed using the measures of length of initial hospitaliz
Keywords: Affective Symptoms; Hospitals, Psychiatric; Human; Length of Stay; Male; Neurotic Disorders; Outcome and Process Assessment (Health Care); Personality Disorders; Prognosis; Schizophrenia; Schizophrenic Psychology; Social Adjustment; Support, U.S. Gov't, P.H.S.; affective neurosis; central nervous system; dept.psy; hospitalization; major clinical study; neurosis; personality disorder; schizophrenia; sociology; therapy

Normal development and psychopathological impairment of the concept of the object on the Rorschach. - Blatt, Sidney J.; Brenneis, C. Brooks; Schimek, Jean G.; Glick, Marion (Journal of Abnormal Psychology, 1976)
Keywords: dept.psy

Preferences for and against stimuli paired with food - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1999)
Pigeons were presented with a concurrent-chains schedule in which terminal-link entries were assigned to two response keys on a percentage basis. The terminal links were fixed delays that sometimes ended with food and sometimes did not. In most conditions, 80% of the terminal links were assigned to one key, but a smaller percentage of the terminal links ended with food for this key, so the number of food reinforcers delivered by the two alternatives was equal. When the same terminal-link stimuli (orange houselights) were used for both alternatives, the pigeons showed a preference for whichever alternative delivered more frequent terminal links. When different terminal-link stimuli (green vs. red houselights) were used for the two alternatives, the pigeons showed a preference for whichever alternative delivered fewer terminal links when terminal-link durations were long, and no systematic preferences when terminal-link durations were short. This pattern of results was consistent with the predictions of Grace's (1994) contextual choice model. Preference for the alternative that delivered more frequent terminal links was usually stronger in the first few sessions of a condition than at the end of a condition, suggesting that the conditioned reinforcing effect of the additional terminal-link presentations was, in part, transitory.
Keywords: *Choice Behavior/ph [Physiology]; *Feeding Behavior/px [Psychology]; *Food Preferences; Animals; Behavior, Animal; Behavior, Animal/ph [Physiology]; Choice; Choice Behavior; Columbidae; Concurrent chains; Conditioned reinforcement; Conditioning (Psychology); Conditioning, Psychological; Feeding Behavior; Food Preferences; Key peck; Pigeons; Reinforcement (Psychology); Reinforcement probability; Reinforcement, Psychology; animal; animal behavior; article; conditioning; decision making; dept.psy; feeding behavior; food preference; physiology; pigeons and doves; psychological aspect; reinforcement

Compliance, noncompliance strategies, and the correlates of compliance in 5-year-old japanese and american children - Abe, Jo Ann A; Izard, Carroll E (Social Development, 1999)
The present study compared compliance, noncompliance strategies, and the correlates in 5-year old Japanese and American children were observed during three standardized laboratory procedures. Compliance, noncompliance strategies, and negative affect were coded during Toy Pick Up procedure. Maternal directiveness and mother-directed behaviors were coded during Mother-Child play and Free-play procedures, respectively. A baseline level of play was also obtained during the Free Play procedures to ensure that the children's willingness to engage in the Toy Pick Up procedure would not be confounded with their level of involvement with the toys. Consistent with predictions derived from a review of cross-cultural research on socialization practices, Japanese children showed longer latencies to begin picking up toys in response to maternal requests and were also more likely to engage in the `less skilled' noncompliance strategies of direct defiance and passive noncompliance than American children. The two groups of children did not, however, differ in their level of negative affect during the Toy Pick Up procedure. Contrary to expectations, maternal directiveness was not associated with compliance in either group of children. However, approach behavior to mother during Free Play was inversely correlated with compliance in Japanese, but not American children.
Keywords: Compliance; Cross-cultural; Preschool children; Self-regulation; dept.psy

A comparative study of quiet sleep, active sleep, and waking on the first 2 days of life - Carroll, D.A.; Denenberg, V.H.; Thoman, E.B. (Developmental Psychobiology, 1999)
Direct behavioral observation and motility monitoring procedures provide reliable data, and both are appropriate for sleep/wake state measurements starting immediately after birth. Using these procedures, newborn rats, rabbits, and humans were found to have a greater amount of quiet sleep on the day of birth rather than 24 hr later. Changes in active sleep and wake were inconsistent across the 2 days. The quiet sleep findings are contrary to the developmental course which increases with age. The findings are interpreted as a temporary adaptive response to the stress of the birth process.
Keywords: Animalia; Animals; Animals and human infants; Animals, Newborn; Cross-species sleep; Female; Humans; Infant, Newborn; Male; Motor Activity; Newborn sleep; Oryctolagus cuniculus; Pregnancy; Rabbits; Rats; Sleep Stages; Sleep in neonates; Sleep, REM; Sleep/wake states in neonates; Species Specificity; Wakefulness; adaptive behavior; animal behavior; animal experiment; article; breathing rate; child behavior; dept.psy; human; human experiment; infant; nonhuman; normal human; rabbit; rat; sleep pattern; sleep time; sleep waking cycle; stress

Choice with delayed and probabilistic reinforcers: Effects of prereinforcer and postreinforcer stimuli - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1998)
In Experiment 1, pigeons' pecks on a green key led to a 5-s delay with green houselights, and then food was delivered on 20% (or, in other conditions, 50%) of the trials. Pecks on a red key led to an adjusting delay with red houselights, and then food was delivered on every trial. The adjusting delay was used to estimate indifference points: delays at which the two alternatives were chosen about equally often. Varying the presence or absence of green houselights during the delays that preceded possible food deliveries had large effects on choice. In contrast, varying the presence of the gr een or red houselights in the intertrial intervals had no effects on choice. In Experiment 2, pecks on the green key led to delays of either 5 s or 30 s with green houselights, and then food was delivered on 20% of the trials. Varying the duration of the green houselights on nonreinforced trials had no effect on choice. The results suggest that the green houselights served as a conditioned reinforcer at some rimes but not at others, depending on whether or nor there was a possibility that a primary reinforcer might be delivered. Given this interpretation of what constitutes a conditioned reinforcer, most of the results were consistent with the view that the strength of a conditioned reinforcer is inversely related to its duration.
Keywords: *Choice Behavior/ph [Physiology]; *Conditioning, Psychological/ph [Physiology]; *Reinforcement, Psychology; Animals; Behavior, Animal; Behavior, Animal/ph [Physiology]; Choice; Choice Behavior; Columbidae; Conditioned reinforcement; Conditioning (Psychology); Delay; Key peck; Pigeons; Probability; Reinforcement (Psychology); Time Factors; animal; animal behavior; article; comparative study; conditioning; decision making; dept.psy; physiology; pigeons and doves; reinforcement; time

A longitudinal study of AIDS conversations between mothers and adolescents - Lefkowitz, ES; Kahlbaugh, P; Au, TKF; Sigman, M (Aids Education and Prevention, 1998)
The current study examined the stability of mother-adolescent AIDS conversations. Twenty-four mother-adolescent dyads (9 boys, 15 girls) participated at Time 1 (adolescents aged 10-14 years), and again 2 years later. Mothers and adolescents engaged in a videotaped conversation about AIDS and completed AIDS questionnaires. Conversations were coded for content and the extent to which mothers dominated conversations. Conversational dominance remained stable over time. AIDS knowledge was greater for mothers than adolescents, but it improved over time for adolescents while remaining stable for mothers. Mothers who reported discussing AIDS-related topics with their adolescents had less discrepancy between their own and their children's AIDS knowledge. Conversational dominance at Time 1 predicted discrepancy in AIDS knowledge 2 years later, whereas discrepancy in AIDS knowledge at Time 1 did not predict conversational dominance two years later. These results suggest the importance of interactive conversations as a more effective way of teaching than didactic conversations.
Keywords: dept.psy; ⛔ No DOI found

Procrastination by pigeons with fixed-interval response requirements - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1998)
Two experiments studied the phenomenon of procrastination, in which pigeons chose a larger, more delayed response requirement over a smaller, more immediate response requirement. The response requirements were fixed-interval schedules that did not lead to an immediate food reinforcer, but that interrupted a 55-s period in which food was delivered at random times. The experiments used an adjusting-delay procedure in which the delay to the start of one fixed-interval requirement was varied over trials to estimate an indifference point-a delay at which the two alternatives were chosen about equally often. Experiment 1 found that as the delay to a shorter fixed-interval requirement was increased, the adjusting delay to a longer fixed-interval requirement also increased, and the rate of increase depended on the duration of the longer fixed-interval requirement. Experiment 2 found a strong preference for a fixed delay of 10 s to the start of a fixed-interval requirement compared to a mixed delay of either 0 or 20 s. The results help to distinguish among different equations that might describe the decreasing effectiveness of a response requirement with increasing delay, and they suggest that delayed reinforcers and delayed response requirements have symmetrical but opposite effects on choice.
Keywords: *Behavior, Animal/ph [Physiology]; *Choice Behavior; *Feeding Behavior/px [Psychology]; *Reinforcement Schedule; Animals; Behavior, Animal; Choice; Choice Behavior; Columbidae; Delay; Feeding Behavior; Fixed-interval schedules; Key peck; Models, Psychological; Pigeons; Procrastination; Reinforcement (Psychology); Reinforcement Schedule; Reinforcement, Psychology; Time Factors; animal; animal behavior; article; comparative study; decision making; dept.psy; feeding behavior; physiology; pigeons and doves; psychological aspect; psychological model; reinforcement; time

Choice and Self-Control - Mazur, James E. (Handbook of Research Methods in Human Operant Behavior, 1998)
For several decades, choice has been the focus of considerable research by those who study operant behavior. This is not surprising, because the topics of choice and operant behavior are intimately intertwined. In everyday life, people can choose among a large, almost infinite set of operant behaviors, and they can choose not only which behaviors to perform, but under what conditions, at what rate, and for how long. Because choice is an essential part of human (and animal) life, it has been studied with great interest not only by behavioral psychologists, but also by decision theorists, economists, political scientists, biologists, and others. The research methods used in these different disciplines vary widely, and a review of all of the different methods for studying choice is well beyond the scope and purpose of this chapter. Instead, the chapter will focus on the techniques most frequently used in operant research—techniques that involve single-subject designs, that allow precise control of the reinforcement contingencies, and that produce (in most cases) large and clear effects on each subject’s behavior.
Keywords: Conditioned Reinforcer; Discriminative Stimulus; Indifference Point; Reinforcement Schedule; Terminal Link; dept.psy

Effects of Rate of Reinforcement and Rate of Change on Choice Behaviour in Transition - Mazur, J.E. (Quarterly Journal of Experimental Psychology Section B: Comparative and Physiological Psychology, 1997)
In two experiments with pigeons, a single variable-interval schedule assigned reinforcers to two response keys on a percentage basis. The percentage of reinforcers assigned to each key was changed every few sessions, and subjects' choice responses were recorded before and after each change. In Experiment 1, the overall rate of reinforcement was varied across conditions The pigeons' choice responses adapted more quickly to a change in the reinforcement percentages when the overall reinforcement rates were higher, but acquisition rates varied by only about a factor of 3, whereas reinforcement rates were varied by about a factor of 9. In Experiment 2, the reinforcement percentages changed about every 8 sessions in Phases 1 and 3, but every 1 or 2 sessions in Phase 2. Pigeons' choice responses adapted to a change in reinforcement percentages more quickly in Phase 2 than in Phases 1 and 3. The results from both experiments pose difficulties for several prominent models of transitional choice behaviour. The results suggest that each successive reinforcer has more impact on a subject's subsequent choice behaviour when the overall rate of reinforcement is lower and when the reinforcement contingencies have changed frequently in the recent past.
Keywords: *Choice Behavior; *Reinforcement, Psychology; Animals; Behavior, Animal; Choice Behavior; Columbidae; Reinforcement (Psychology); animal; animal behavior; article; comparative study; decision making; dept.psy; pigeons and doves; reinforcement; ⛔ No DOI found

Comparative affective reactivity of different types of communication disturbances in schizophrenia - Docherty, Nancy M; Hebert, Anthony S (Journal of Abnormal Psychology, 1997)
Keywords: dept.psy

Basic and applied research on choice responding - Fisher, Wayne W; Mazur, James E (Journal of Applied Behavior Analysis, 1997)
Choice responding refers to the manner in which individuals allocate their time or responding among available response options. In this article, we first review basic investigations that have identified and examined variables that influence choice responding, such as response effort and reinforcement rate, immediacy, and quality. We then describe recent bridge and applied studies that illustrate how the results of basic research on choice responding can help to account for human behavior in natural environments and improve clinical assessments and interventions.
Keywords: dept.psy

The affective nature of Mother–Adolescent communication concerning sexuality and conflict - Kahlbaugh, Patricia E; Lefkowitz, Eva S; Valdez, Patricia; Sigman, Marian (Journal of Research on Adolescence, 1997)
This 2-year longitudinal study examined the affective nature of communication between mothers and adolescents from early to mid-adolescence. Eleven-to 16-year-old adolescents and their mothers were videotaped while engaging in conversations about everyday topics, dating and sexuality, and conflicts. Nonverbal displays of affiliation, embarrassment, and contempt were found to be fairly stable across conversations, across members of the same dyad, and across time for the mothers. However, there were some effects of conversational topic in that adolescents displayed less affiliation in the conflict conversation than in the other conversations during the 1st session. In addition, boys displayed more contempt when talking about dating and sexuality than about conflicts. Over the 2-year period, the level of affiliation decreased for adolescents, and maternal conversational dominance increased. In all conversations and at both time periods, adolescents displayed more embarrassment and contempt and less affiliation than did mothers. Both maternal and adolescent levels of affiliation during the conversations in the 1st session predicted degree of satisfaction with certain family characteristics expressed in the 2nd session. Copyright © 1997, Lawrence Erlbaum Associates, Inc.
Keywords: dept.psy

Choice, delay, probability, and conditioned reinforcement - Mazur, James E (Animal Learning & Behavior, 1997)
The hyperbolic-decay model is a mathematical expression of the relation between delay and reinforcer value. The model has been used to predict choices in discrete-trial experiments on delay-amount tradeoffs, on preference for variable over fixed delays, and on probabilistic reinforcement. Experiments manipulating the presence or absence of conditioned reinforcers on trials that end without primary reinforcement have provided evidence that the hyperbolic-decay model actually predicts the strength of conditioned reinforcers rather than the strength of delayed primary reinforcers. The model states that the strength of a conditioned reinforcer is inversely related to the time spent in its presence before a primary reinforcer is delivered. A possible way to integrate the model with Grace's (1994) contextual-choice model for concurrent-chain schedules is presented. Also discussed are unresolved difficulties in determining exactly when a stimulus will or will not serve as a conditioned reinforcer.
Keywords: article; behavior; conditioning; decision making; dept.psy; model; nonhuman; reinforcement; theory

Choice with certain and uncertain reinforcers in an adjusting-delay procedure - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1996)
A discrete-trials adjusting-delay procedure was used to investigate the conditions under which pigeons might show a preference for partial reinforcement over 100% reinforcement, an effect reported in a number of previous experiments. A peck on a red key always led to a delay with red houselights and then food. In each condition, the duration of the red-houselight delay was adjusted to estimate an indifference point. In 100% reinforcement conditions, a peck on a green key always led to a delay with green houselights and then food. In partial-reinforcement conditions, a peck on the green key led either to the green houselights and food or to white houselights and no food. In some phases of the experiment, statistically significant preference for partial reinforcement over 100% reinforcement was found, but this effect was observed in only about half of the pigeons. The effect was largely eliminated when variability in the delay stimulus colors was equated for 50% reinforcement conditions and 100% reinforcement conditions. Idiosyncratic preferences for certain colors or for stimulus variability may be at least partially responsible for the effect.
Keywords: *Appetitive Behavior; *Choice Behavior; *Motivation; Animals; Appetitive Behavior; Choice; Choice Behavior; Color Perception; Columbidae; Conditioned reinforcers; Key peck; Motivation; Pigeons; Reinforcement Schedule; Reinforcement delay; Reinforcement probability; animal; appetite; article; color vision; decision making; dept.psy; motivation; pigeons and doves; reinforcement; ❓ Multiple DOI

Turn-taking in mother-adolescent conversations about sexuality and conflict - Lefkowitz, Eva S; Kahlbaugh, Patricia E; Sigman, Marian (Journal of Youth and Adolescence, 1996)
The current study examined the nature and style of mother-adolescent conversations, how these conversations differ by subject matter and dyadic and individual differences. Thirty-one mother-adolescent dyads (17 boys, 14 girls) with a child between the ages of 11 and 14 had a nonstructured conversation and conversations about conflict and sexuality They also completed questionnaires on beliefs about acquired immunodeficiency syndrome (AIDS). Conversations were measured for turn taking, total number of words, and conversational dominance, as well as nonverbal measures of affiliation, shame, and contempt Conversations about sexuality involved less turn taking, fewer words, and more mother dominance than nonstructured conversations. Conversations about conflicts involved less turn taking but more words than nonstructured conversations Some gender and age differences were found. Move interactive conflict conversations contained higher levels of affiliation, and lower levels of child shame than conversations with fewer turns or higher mother dominance. In addition, children in move interactive dyads possessed a larger percentage of their mother's AIDS knowledge, and worried about AIDS a moderate amount.
Keywords: dept.psy

To forget or not to forget: The effect of probability of test on directed forgetting - Golding, JM; Roper, KL; Hauselt, J (Quarterly Journal of Experimental Psychology Section a-Human Experimental Psychology, 1996)
Two experiments investigated how individuals use explicit memory cues that designate different probabilities of test. As in typical directed forgetting studies, subjects received words explicitly cued as having either a 0% or a 100% chance of being on a subsequent memory test (i.e. forget and remember cues, respectively). In addition, some words were explicitly cued as having the potential to be either forgotten or remembered (i.e. a 50% cue). Recall of 50% words was between that of 0% and 100% words. In addition, the presence of 50% words lowered recall of the 100% words compared to that of a control group that did not receive the 50% words, but received the same number of 100% words. A think-aloud task indicated that these results were due to the 50% words being treated like either 100% or 0% words at encoding. The results are discussed in terms of the effect of different probabilities of test on the strategic processing and representation of information.
Keywords: Adult; Attention; Female; Humans; Male; Mental Recall; Probability Learning; Verbal Learning; adult; article; attention; dept.psy; female; human; learning; male; recall

Past experience, recency, and spontaneous recovery in choice behavior - Mazur, James E (Learning & Behavior, 1996)
Pigeons' responses on two keys were recorded before and after the percentage of reinforcers delivered by each key was changed. In each condition of Experiment 1, the reinforcement percentage for one key was 50% for several sessions, then either 70% or 90% for one, two, or three sessions, and then 50% for another few sessions. At the start of the second and third sessions after a change in reinforcement percentages, choice percentages often exhibited spontaneous recovery-a reversion to the response percentages of earlier sessions. The spontaneous recovery consisted of a shift toward a more extreme response percentage in some cases and toward a less extreme response percentage in other cases, depending on what reinforcement percentages were previously in effect. In Experiment 2, some conditions included a 3-day rest period before a change in reinforcement percentages, and other conditions included no such rest days. Slightly less spontaneous recovery was observed in conditions with the rest periods, suggesting that the influence of prior sessions diminished with the passage of time. The results are consistent with the view that choice behavior at the start of a new session is based on a weighted average of the events of the past several sessions.
Keywords: Animalia; Columba; animal behavior; animal experiment; article; computer simulation; conditioning; decision making; dept.psy; experience; feeding; model; nonhuman; pigeon; reinforcement; reliability

STIR Success Through Individual Recreation: Working with the low-functioning resident with dementia or Alzheimer's disease: - Russen-Rondinone, Tonya; DesRoberts, Anne-Marie M. (American Journal of Alzheimer's Disease, 1996)
STIR, Success Through Individual Recreation is examined to determine the benefits of individualized recreational activities geared towards the lower functioning...
Keywords: dept.psy

Procrastination by pigeons: Preference for larger, more delayed work requirements - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1996)
In three experiments, pigeons chose between alternatives that required the completion of a small ratio schedule early in the trial or a larger ratio schedule later in the trial. Completion of the ratio requirement did not lead to an immediate reinforcer, but simply allowed the events of the trial to continue. In Experiment 1, the ratio requirements interrupted periods in which food was delivered on a variable-time schedule. In Experiments 2 and 3, each ratio requirement was preceded and followed by a delay, and only one reinforcer was delivered, at the end of each trial. Two of the experiments used an adjusting-ratio procedure in which the ratio requirement was increased and decreased over trials so as to estimate an indifference point-a ratio size at which the two alternatives were chosen about equally often. These experiments found clear evidence for `'procrastination”-the choice of a larger but more delayed response requirement. In some cases, subjects chose the more delayed ratio schedule even when it was larger than the more immediate alternative by a factor of four or more. The results suggest that as the delay to the start of a ratio requirement is increased, it has progressively less effect on choice behavior, in much the same way that delaying a positive reinforcer reduces it effect on choice.
Keywords: *Appetitive Behavior; *Conditioning, Operant; *Motivation; *Reinforcement Schedule; Animals; Appetitive Behavior; Attention; Choice; Choice Behavior; Columbidae; Conditioning, Operant; Delay; Inhibition (Psychology); Inhibition, Psychological; Key peck; Motivation; Pigeons; Problem Solving; Procrastination; Ratio schedules; Reinforcement Schedule; animal; appetite; article; attention; decision making; dept.psy; inhibition (psychology); instrumental conditioning; motivation; pigeons and doves; problem solving; reinforcement

The process of answering direction‐giving questions when someone is lost on a university campus: The role of pragmatics - Golding, Jonathan M; Graesser, Arthur C; Hauselt, Jerry (Applied Cognitive Psychology, 1996)
Two experiments investigated how college students answered direction-giving questions when a confederate asked for directions to a destination on a university campus. The experiments applied the QUEST model (Graesser and Franklin, 1990) to direction giving, emphasizing the pragmatic component of the model that focuses on establishing common ground and dealing with the questioner's goals. The two experiments had different articulations of the direction-giving question (i.e.'How do you get to destination X?' versus `Where is destination X?'), and a different destination. The answers generated by subjects supported both aspects of the pragmatic component.
Keywords: dept.psy

Conditioned reinforcement and choice with delayed and uncertain primary reinforcers - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1995)
In an adjusting-delay choice procedure, pigeons could peck on either a red key or a green key. A peck on the red key always led to a delay associated with red houselights and then food. The delay was adjusted over trials to estimate an indifference point-a delay at which the two keys were chosen about equally often. In some conditions, a peck on the green key led to food on all trials after delays of either 10 a or 30 s, and green houselights were lit during the delays. In other conditions, food was presented on only half of the green-key trials. If the green houselights continued to occur on both reinforcement and nonreinforcement trials, preference for the green key always decreased. Preference for the green key also decreased if half of the trials had 30-s houselights followed by food and the other half had no green houselights and no food. However, preference for the green key actually increased if half of the trials had 10-s green houselights followed by food and the other half had no green houselights followed by no food. The latter condition therefore demonstrated a case in which preference for an alternative increased when food was removed from half of the trials. The results suggest that the red and green houselights served as conditioned reinforcers. A hyperbolic decay model (Mazur, 1989) provided good predictions for all conditions by assuming that the strength of a conditioned reinforcer is inversely related to the total time spent in its presence before food is delivered.
Keywords: Animal; Association Learning; Choice Behavior; Color Perception; Conditioning, Operant; Discrimination Learning; Mental Recall; Motivation; Pigeons; Reinforcement Schedule; Retention (Psychology); Support, U.S. Gov't, P.H.S.; animal; article; choice; color vision; conditioned reinforcement; decision making; delay of reinforcement; dept.psy; discrimination learning; instrumental conditioning; key peck; learning; long term memory; motivation; pigeon; pigeons; probability of reinforcement; recall; reinforcement

Development of preference and spontaneous recovery in choice behavior with concurrent variable-interval schedules - Mazur, James E (Animal Learning & Behavior, 1995)
Pigeons pecked on two response keys that delivered reinforcers on a variable-interval schedule. The proportion of reinforcers delivered by one key was constant for a few sessions and then changed, and subjects' choice responses were recorded during these periods of transition. In Experiment 1, response proportions approached a new asymptote slightly more slowly when the switch in reinforcement proportions was more extreme. In Experiment 2, slightly faster transitions were found with higher overall rates of reinforcement. The results from the first session, after a switch in the reinforcement proportions, were generally consistent with a mathematical model that assumes that the strength of each response is increased by reinforcement and decreased by nonreinforcement. However, neither this model nor other similar models; predicted the `'spontaneous recovery” observed in later sessions: At the start of these sessions, response proportions reverted toward their preswitch levels. Computer simulations could mimic the spontaneous recovery by assuming that subjects store separate representations of response strength for each session, which are averaged at the start of each new session.
Keywords: animal behavior; article; decision making; dept.psy; mathematical model; nonhuman; pigeon; reinforcement

Developmental differences in the symptomatology of psychiatric-inpatients with and without mild mental-retardation - Glick, M; Zigler, E (American Journal on Mental Retardation, 1995)
The symptomatology of psychiatric inpatients with mild mental retardation was compared with that of a matched sample of inpatients without mental retardation. An integration of the developmental position on mental retardation with the developmental approach to adult psychopathology generated the hypotheses that, compared to patients without mental retardation, patients with mild mental retardation would display (a) more symptoms indicative of turning against others and fewer symptoms indicative of turning against the self, (b) more symptoms involving expression in action rather than thought, and (c) psychotic symptom pictures that more frequently involve hallucinations without delusions and infrequently involve delusions alone. All hypotheses were confirmed.
Keywords: *Intellectual Disability/co [Complications]; *Mental Disorders/co [Complications]; Adult; Delusions/et [Etiology]; Female; Hallucinations/et [Etiology]; Hospitalization; Hospitals, Psychiatric; Humans; Male; Mental Disorders/px [Psychology]; Mental Disorders/rh [Rehabilitation]; dept.psy; ⛔ No DOI found

Effects of intertrial reinforcers on self-control choice. - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1994)
In three experiments, pigeons chose between a small amount of food delivered after a short delay and a larger amount delivered after a longer delay. A discrete-trial adjusting-delay procedure was used to estimate indifference points-pairs of delay-amount combinations that were chosen about equally often. In Experiment 1, when additional reinforcers were available during intertrial intervals on a variable-interval schedule, preference for the smaller, more immediate reinforcer increased. Experiment 2 found that this shift in preference occurred partly because the variable-interval schedule started sooner after the smaller, more immediate reinforcer, but there was still a small shift in preference when the durations and temporal locations of the variable-interval schedules were identical for both alternatives. Experiment 3 found greater increases in preference for the smaller, more immediate reinforcer with a variable-interval 15-s schedule than with a variable-interval 90-s schedule. The results were generally consistent with a model that states that the impact of any event that follows a choice response declines according to a hyperbolic function with increasing time since the moment of choice.
Keywords: Animal; Appetitive Behavior; Choice Behavior; Color Perception; Conditioning, Operant; Mental Recall; Motivation; Pigeons; Reinforcement Schedule; Support, Non-U.S. Gov't; Support, U.S. Gov't, P.H.S.; animal; appetite; article; color vision; decision making; dept.psy; instrumental conditioning; intertrial reinforcers; key peck; motivation; pigeon; pigeons; recall; reinforcement; reinforcer amount; reinforcer delay; self‐control

Anhedonia and premorbid competence in young, nonpsychotic psychiatric inpatients. - Garnet, Kathleen E; Glick, Marion; Edell, William S (Journal of Abnormal Psychology, 1993)
Earlier studies have demonstrated a significant relation between scores on the Physical Anhedonia Scale-but not on the Perceptual Aberration Scale-and premorbid social adjustment in schizophrenics (Chapman, Chapman, & Raulin, 1976, 1978; Schuck, Leventhal, Rothstein, & Irizarry, 1984). A similar relation between scores on these 2 scales and interpersonal competence in college students has also been noted (Beckfield, 1985; Haberman, Chapman, Numbers, & McFall, 1979; Numbers & Chapman, 1982). The present study extends this work by examining the relation of premorbid adjustment to scores on these 2 scales among young, nonpsychotic psychiatric inpatients. Consistent with the earlier findings, anhedonic Ss had poorer premorbid social competence when compared with nonanhedonic Ss, whereas no relation was found between scores on perceptual aberration and premorbid social competence.
Keywords: Adolescent; Adult; Affective Symptoms; Female; Hospitalization; Human; Interpersonal Relations; Male; Perceptual Distortion; Personality Inventory; Psychiatric Status Rating Scales; Schizophrenia; Schizophrenic Psychology; Social Adjustment; adolescent; adult; article; competence; dept.psy; female; human; major clinical study; male; mental patient; neurosis; perception disorder; schizophrenia; social adaptation

Predicting the strength of a conditioned reinforcer: effects of delay and uncertainty: - Mazur, James E (Current Directions in Psychological Science, 1993)
Keywords: dept.psy

Choice with delayed and probabilistic reinforcers: effects of variability, time between trials, and conditioned reinforcers - Mazur, James E; Romano, Angela (Journal of the Experimental Analysis of Behavior, 1992)
In a discrete-trials procedure with pigeons, a response on a green key led to a 4-s delay (during which green houselights were lit) and then a reinforcer might or might not be delivered. A response on a red key led to a delay of adjustable duration (during which red houselights were lit) and then a certain reinforcer. The delay was adjusted so as to estimate an indifference point-a duration for which the two alternatives were equally preferred. Once the green key was chosen, a subject had to continue to respond on the green key until a reinforcer was delivered. Each response on the green key, plus the 4-s delay that followed every response, was called one “link” of the green-key schedule. Subjects showed much greater preference for the green key when the number of links before reinforcement was variable (averaging four) than when it was fixed (always exactly four). These findings are consistent with the view that probabilistic reinforcers are analogous to reinforcers delivered after variable delays. When successive links were separated by 4-s or 8-s “interlink intervals” with white houselights, preference for the probabilistic alternative decreased somewhat for 2 subjects but was unaffected for the other 2 subjects. When the interlink intervals had the same green houselights that were present during the 4-s delays, preference for the green key decreased substantially for all subjects. These results provided mixed support for the view that preference for a probabilistic reinforcer is inversely related to the duration of conditioned reinforcers that precede the delivery of food.
Keywords: Animal; Behavior, Animal; Choice Behavior; Competitive Behavior; Conditioning, Operant; Female; Instinct; Male; Models, Psychological; Pigeons; Reinforcement (Psychology); Reinforcement Schedule; Spatial Behavior; Support, U.S. Gov't, P.H.S.; animal; animal behavior; article; behavior; choice; competitive behavior; conditioned reinforcement; decision making; delay of reinforcement; dept.psy; drive; female; instrumental conditioning; key peck; male; model; pigeon; pigeons; probability of reinforcement; reinforcement

Choice behavior in transition : development of preference with ratio and interval schedules - Mazur, James E (Journal of Experimental Psychology: Animal Behavior Processes, 1992)
In Experiment 1, the choice responses of 8 pigeons were observed during 50 periods of transition. Each condition began with equal probabilities of reinforcement on 2 response keys and switched to unequal probabilities. With the ratio of the 2 probabilities held constant, preference for the higher probability developed more rapidly when the 2 probabilities were high than when they were low. In Experiment 2, each condition began with 2 equal variable-interval schedules, but later 1 key delivered 60%, 75%, or 90% of the reinforcers. The rate of approach to asymptotic performance was roughly the same with all 3 reinforcement percentages. These and previous results pose difficulties for some well-known models of acquisition, but the results are well described by a simple model that states that the strength of each response is independently increased by reinforcement and decreased by nonreinforcement.
Keywords: dept.psy

Personal privacy and access to information on a college campus - a preliminary-report - Tolchin, G (Psychology, 1992)
A survey of college students concerning their knowledge and attitudes towards informational privacy was conducted. Virtually all subjects surveyed considered their personal privacy to be important to them. However, the survey results suggest considerable misunderstanding and misinformation regarding informational privacy. In addition, students showed little faith that their personal information was being securely protected against unauthorized disclosure. Indeed, they seemed to expect a considerable measure of privacy violation with respect to their student records.
Keywords: dept.psy; ⛔ No DOI found

Choice behavior in transition: Development of preference in a free-operant procedure - Mazur, James E; Ratti, Theresa A (Learning & Behavior, 1991)
Twenty acquisition curves were obtained from each of 8 pigeons in a free-operant choice procedure. Every condition began with a phase in which two response keys had equal probabilities of reinforcement, and, as a result, subjects' responses were divided fairly evenly between the two keys. This was followed by a phase in which one key had a higher probability of reinforcement than the other, and the development of preference was observed. In all but a few cases, response proportions increased for the key with the higher probability of reinforcement. In most conditions, the two probabilities differed by .06, but the actual probabilities varied (from .16 and .10 in one condition to .07 and .01 in another). Development of preference for the key with the higher probability of reinforcement was slower when the ratio of the two reinforcement probabilities was small (.16/.10) than when it was large (.07/.01). This finding is inconsistent with the predictions of several different quantitative models of acquisition, including the kinetic model (Myerson & Miezin, 1980) and the ratio-invariance model (Horner & Staddon, 1987). However, the finding is consistent with a hypothesis based on Weber's law, which states that the two alternatives are more discriminable when the ratio of their reinforcement probabilities is larger, and, as a result, the acquisition of preference is faster.
Keywords: animal experiment; article; behavior; conditioned reflex; dept.psy; discrimination learning; instrumental conditioning; kinetics; model; nonhuman; pigeon; probability; reinforcement

Straining the word “optimal” - Mazur, James E (Behavioral and Brain Sciences, 1991)
Keywords: dept.psy

Choice with probabilistic reinforcement: effects of delay and conditioned reinforcers. - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1991)
Two experiments measured pigeons' choices between probabilistic reinforcers and certain but delayed reinforcers. In Experiment 1, a peck on a red key led to a 5-s delay and then a possible reinforcer (with a probability of .2). A peck on a green key led to a certain reinforcer after an adjusting delay. This delay was adjusted over trials so as to estimate an indifference point, or a duration at which the two alternatives were chosen about equally often. In all conditions, red houselights were present during the 5-s delay on reinforced trials with the probabilistic alternative, but the houselight colors on nonreinforced trials differed across conditions. Subjects showed a stronger preference for the probabilistic alternative when the houselights were a different color (white or blue) during the delay on nonreinforced trials than when they were red on both reinforced and nonreinforced trials. These results supported the hypothesis that the value or effectiveness of a probabilistic reinforcer is inversely related to the cumulative time per reinforcer spent in the presence of stimuli associated with the probabilistic alternative. Experiment 2 tested some quantitative versions of this hypothesis by varying the delay for the probabilistic alternative (either 0 s or 2 s) and the probability of reinforcement (from .1 to 1.0). The results were best described by an equation that took into account both the cumulative durations of stimuli associated with the probabilistic reinforcer and the variability in these durations from one reinforcer to the next.
Keywords: Animal; Attention; Choice Behavior; Color Perception; Conditioning, Operant; Mental Recall; Pigeons; Probability Learning; Reinforcement Schedule; Support, U.S. Gov't, P.H.S.; Time Perception; adjusting schedule; animal; article; attention; color vision; conditioned reinforcement; decision making; dept.psy; instrumental conditioning; key peck; learning; pigeon; pigeons; recall; reinforcement; reinforcer delay; reinforcer probability; time perception

Choice behavior in transition: development of preference for the higher probability of reinforcement - Bailey, John T.; Mazur, James E. (Journal of the Experimental Analysis of Behavior, 1990)
Ten acquisition curves were obtained from each of 4 pigeons in a two‐choice discrete‐trial procedure. In each of these 10 conditions, the two response keys initially had equal probabilities of reinforcement, and subjects' choice responses were about equally divided between the two keys. Then the reinforcement probabilities were changed so that one key had a higher probability of reinforcement (the left key in half of the conditions and the right key in the other half), and in nearly every case the subjects developed a preference for this key. The rate of acquisition of preference for this key was faster when the ratio of the two reinforcement probabilities was higher. For instance, acquisition of preference was faster in conditions with reinforcement probabilities of .12 and .02 than in conditions with reinforcement probabilities of .40 and .30, even though the pairs of probabilities differed by .10 in both cases. These results were used to evaluate the predictions of some theories of transitional behavior in choice situations. A trial‐by‐trial analysis of individual responses and reinforcers suggested that reinforcement had both short‐term and long‐term effects on choice. The short‐term effect was an increased probability of returning to the same key on the one or two trials following a reinforcer. The long‐term effect was a gradual increase in the proportion of responses on the key with the higher probability of reinforcement, an increase that usually continued for several hundred trials. 1990 Society for the Experimental Analysis of Behavior
Keywords: Animal; Attention; Choice Behavior; Color Perception; Discrimination Learning; Motivation; Orientation; Pigeons; Probability Learning; Reinforcement Schedule; Support, U.S. Gov't, P.H.S.; acquisition; animal; article; attention; choice; color vision; decision making; dept.psy; discrimination learning; key peck; learning; motivation; orientation; pigeon; pigeons; probability of reinforcement; reinforcement

Differences across gender, grade level, and academic track in the content of the ideal self-image - Bybee, Jane; Glick, Marion; Zigler, Edward (Sex Roles, 1990)
Students from the 5th, 8th, and 11th grades (55 male and 53 female) were asked to describe their ideal self-image. Analyses revealed a number of gender and developmental differences not found with other self-image measures. A greater proportion of females than males mentioned two of the categories related to family life: marriage and improving relations with their family of origin. Mentions of categories surrounding athletics were more prevalent among males. Grade level differences in the content of the ideal self-image reflected cognitive-developmental shifts away from concrete descriptors, changes in physical maturity and the heightened importance of peer relationships around adolescence, and the approach of developmental milestones. Fewer students mentioned physical appearance at higher grade levels. Mentions of athletic abilities and social acceptance peaked at the 8th grade, while mentions of college, marriage, and having children rose at higher grade levels. Differences in the content areas mentioned by average versus advanced track students appeared to reflect differences in both cognitive-developmental level and socialization experiences. © 1990 Plenum Publishing Corporation.
Keywords: dept.psy

Choice between delayed reinforcers and fixed‐ratio schedules requiring forceful responding - Mazur, James E; Kralik, J D (Journal of the Experimental Analysis of Behavior, 1990)
This experiment measured pigeons' choices between delayed reinforcers and fixed‐ratio schedules in which a force of approximately 0.48 N was needed to operate the response key. In ratio‐delay conditions, subjects chose between a fixed‐ratio schedule and an adjusting delay. The delay was increased or decreased several times a session in order to estimate an indifference point—a delay duration at which the two alternatives were chosen about equally often. Each ratio‐delay condition was followed by a delay‐delay condition in which subjects chose between the adjusting delay and a variable‐time schedule, with the components of this schedule selected to match the ratio completion times of the preceding ratio‐delay condition. The adjusting delays at the indifference point were longer when the alternative was a fixed‐ratio schedule than when it was a matched variable‐time schedule, which indicated a preference for the matched variable‐time schedules over the fixed‐ratio schedules. This preference increased in a nonlinear manner with increasing ratio size. This nonlinearity was inconsistent with a theory that states that indifference points for both time and ratio schedules can be predicted by multiplying the choice response‐reinforcer intervals of the two types of schedules by different multiplicative constants. Two other theories, which predict nonlinear increases in preference for the matched variable‐time schedules, are discussed. 1990 Society for the Experimental Analysis of Behavior
Keywords: Animal; Choice Behavior; Conditioning, Classical; Exertion; Memory; Mental Recall; Motivation; Pigeons; Psychomotor Performance; Reinforcement Schedule; Support, U.S. Gov't, P.H.S.; adjusting procedure; animal; article; conditioned reflex; decision making; dept.psy; exercise; fixed ratio; key peck; memory; motivation; pigeon; pigeons; psychomotor performance; recall; reinforcement; reinforcer delay; response effort; variable time

A longitudinal study of emotion expression and personality relations in early development - Abe, J.A.A.; Izard, C.E. (Journal of Personality and Social Psychology, 1999)
To investigate emotion expression and personality relations, the authors coded infants' full-face and component positive and negative expressions during Episodes 4 through 8 of the strange situation procedure at age 18 months and obtained maternal ratings of the 5-factor model of personality when children were 3.5 years old. Full-face negative expression was directly related to Neuroticism and inversely related to Agreeableness and Conscientiousness. By contrast, component positive expression showed the exact opposite pattern of relations. Full-face positive expression was positively correlated with Extraversion and Openness to Experience. These findings indicate that full-face and component expressions may index different intensities of emotions. Emotion expression and personality relations were not mediated by the security of attachment continuum or the emotional reactivity dichotomy derived from the attachment subclassifications.
Keywords: *Emotions; *Personality; Age Factors; Child, Preschool; Emotions; Female; Humans; Longitudinal Studies; Male; Personality; age; article; dept.ils; dept.psy; emotion; female; human; longitudinal study; male; personality; preschool child